Clinical characteristics and short-term outcomes of pediatric lymphoma: a retrospective cohort study from a large tertiary hospital in a low- and middle-income country - Dania Abuhalima; Dima Malhis; Zeina Qadi; Adham Abu Taha; Sultan Mosleh; Sa’ed H. Zyoud (Scientific Reports, 2025)
Abstract The incidence of childhood cancer has increased, with lymphoma being the third most common malignancy in children and showing improved survival rates. This study aimed to analyse the demographic, clinical, and outcome data of pediatric lymphoma patients, compare the characteristics of the HL and NHL subtypes, and evaluate treatment outcomes. A single-center retrospective cohort study was conducted at An-Najah National University Hospital (NNUH) in Palestine from 2013 to 2023. Seventy-five pediatric patients (≤ 18 years) newly diagnosed with Hodgkin lymphoma (HL) or non-Hodgkin lymphoma (NHL) were included, and data from electronic medical records were used. Follow-up data were analysed via Kaplan–Meier survival curves to determine event-free survival (EFS) and overall survival (OAS).This study revealed a male predominance in both NHL (1.9:1) and HL (1.3:1) patients, with a mean age of 9 years for NHL patients and 10 years for HL patients. The majority of patients were from the West Bank (56%) or Gaza (44%). NHL patients commonly presented with GI symptoms (31.7%), whereas HL patients (70.6%) presented with neck masses. B symptoms were more common in HL patients (55.9%). The tumor stage also differed, with NHL often being stage III and HL being stage II. The predominant subtypes were Burkitt’s lymphoma (BL) for NHL and classical nodular sclerosis for HL. Overall survival was 96%, with 4% mortality. During the follow-up period (mean 26.5 ± 18 months), 84% of the patients had events, with 86.7% of patients remaining event-free. Relapse occurred in 13.3% of patients, predominantly in the NHL group, and the prevalence of OAS was 96%. The 2-year event-free survival (EFS) rate was 85.1%, and the 2-year overall survival (OAS) rate was 96.6%, as estimated via Kaplan‒Meier survival analysis. Our study provides insights into the clinical characteristics and short-term outcomes of pediatric lymphoma patients in Palestine. Pediatric lymphoma is more common in males and primarily affects children over 10 years of age. HL is less prevalent, has a higher survival rate, and most commonly presents with a neck mass. In contrast, NHL is more common, is associated with higher relapse and mortality rates, and often presents with gastrointestinal symptoms. Burkitt’s lymphoma (BL) is the most common NHL subtype and is not strongly associated with B symptoms. These findings emphasize the importance of early diagnosis and continuous follow-up in optimizing treatment outcomes. Further studies with larger cohorts and longer follow-up periods are needed to validate these findings and assess long-term survival and cure rates.